Little reason to call them small noncoding RNAs - Ferrara, Silvia; Brignoli, Tarcisio; Bertoni, Giovanni (Frontiers in Microbiology, 2023)
Hundreds of different species of small RNAs can populate a bacterial cell. This small transcriptome contains important information for the adaptation of cellular physiology to environmental changes. Underlying cellular networks involving small RNAs are RNA-RNA and RNA-protein interactions, which are often intertwined. In addition, small RNAs can function as mRNAs. In general, small RNAs are referred to as noncoding because very few are known to contain translated open reading frames. In this article, we intend to emphasize highlight that the number of small RNAs that fall within the set of translated RNAs is bound to increase. In addition, we aim to emphasize that the dynamics of the small transcriptome involve different functional codes, not just the genetic code. Therefore, since the role of small RNAs is always code-driven, we believe that there is no reason to continue calling them small noncoding RNAs.